Archipelascape A Master Plan For Regenerating The Archipelagic Country - Budi Prayitno (Universitas Bandar Lampung (UBL), 2010)
The regeneration of coastal cities is one of the key architectural, urban design and planning innovation with the of industrial decline, enhance livability and sustainability and transform the image of the Indonesian archipelagic and marine decline. Thus, the various design and planning model for waterfront regeneration could be able to develop and expand into mixed-use and hybrid function which invent new conjunction of public and private interest.Â In this emerging waterfront projects, inter-coastal cities competition turns the city into a product which is marketed and sold, focusing attention on the imagery which iconed the city and differentiates it from other coastal cities. Such images includes iconography of local waterfront and function is linked to the rise brand marketing in the archipelagic context.These planning activities show there have been a wide array of responses theÂ opportunities and problems associated with spatial networks of coastal areas of metropolitan cities. They recognize a process starting with growing the nodes (coastal activities centers) and clustering some sub spatial networks through bridging them by water transportation systems. This process is shaped by creating multi-layered network of regional coastal cities into some clusters and corridors in the context of waterfront metropolitan regeneration in archipelagic country.Â There are three level of network in archipelagic spatial planning concepts that is cities network, regional network (intra-island and inter-island) and global network for fostering the ability of other regions to rival Jakarta city dominance in activities and drawing power. This is only when the regional coastal cities have acquired this power can there be a harmonization of centralized and decentralized planning policy.